1982
DOI: 10.1159/000198793
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Enzyme Activities, Peptide Hormone Concentrations and Hormone Secretory Granule Properties in Functioning Proximal Jejunum after Shunt Operation for Obesity

Abstract: Crosby capsule biopsies were obtained from functioning jejunum in 6 patients between 7 and 15 months after jejuno-ileal bypass for morbid obesity and compared with 6 normal control biopsies. Brush border and other mucosal enzyme activities and seven regulatory peptide concentrations were measured in each biopsy. Analytical subcellular fractionation by sucrose density gradient centrifugation was used to investigate brush border and peptide secretory granule properties. Specific activities of all the brush borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1984
1984
1990
1990

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…This contrast, together with the tendency for the non-func tional ileum to contain slightly more rather than less YY57 immunoreactivity, is not in dicative of a major hypertrophic or other role [3,7,16,35,37] for large glucagon precur sors) in the morphological changes which follow the operations. Dawson et al [7] re ported that the ileal enteroglucagon immuno reactivity was unchanged in the functional ileum of patients who had extensive JIB operations.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This contrast, together with the tendency for the non-func tional ileum to contain slightly more rather than less YY57 immunoreactivity, is not in dicative of a major hypertrophic or other role [3,7,16,35,37] for large glucagon precur sors) in the morphological changes which follow the operations. Dawson et al [7] re ported that the ileal enteroglucagon immuno reactivity was unchanged in the functional ileum of patients who had extensive JIB operations.…”
Section: Discussionmentioning
confidence: 82%
“…This contrast, together with the tendency for the non-func tional ileum to contain slightly more rather than less YY57 immunoreactivity, is not in dicative of a major hypertrophic or other role [3,7,16,35,37] for large glucagon precur sors) in the morphological changes which follow the operations. Dawson et al [7] re ported that the ileal enteroglucagon immuno reactivity was unchanged in the functional ileum of patients who had extensive JIB operations. Our results that ileum contains substantially more N-terminal-to-central im munoreactivity than other gut tissues in rats, agrees with those of Jacobs et al [16], These authors, however, reported that enterogluca gon levels in ileum and plasma of Wistar rats (180-230 g) were elevated by 60% following resection of the proximal two thirds of the small intestine and suggested a 'trophic role in producing intestinal growth'.…”
Section: Discussionmentioning
confidence: 82%
“…Intestinal resection provokes the hypersecretion of gastric acid, probably by increasing gastrin production [1,12,28]. Sorensen et al [20] and Dawson et al [5] found that bypass surgery has no important influence on the levels of gastrin produced. Junghanns et al [10] reported a less pronounced rise of serum gastrin levels after distal resection than after proximal resection (PR) in dogs.…”
Section: Discussionmentioning
confidence: 99%